Emotion and language learning: an exploration of experience and motivation in a Mexican university context - Méndez López, Mariza Guadalupe (2011)
Although there have been numerous studies on motivation in foreign language learning and on emotions in general education, little research in foreign language learning have focused on the relation between motivation and learners' emotions (Maclntyre, 2002), as this shift to the affective side of motivation has only recently been suggested. Thus, this study aims to contribute to the body of knowledge on how foreign language learning motivation is shaped by emotional experiences.